Pemodelan Dan Simulasi Antenna Microstrip Array Single, 1x2, 1x4, Dan 1x8 Elemen Patch Untuk Aplikasi Radar Manpack - Irawan Saputra, Dede; Thaufiq Sabtiawan; Yussi Perdana Saputera (EPSILON: Journal of Electrical Engineering and Information Technology, 2023)
Microstrip antena can be the main choice in various communication applications because it has a fairly light mass and small size when compared to other types of antenas such as dipole antenas, yagi and so on. To know about the workings of radar. Use the CST Studio Suite application to simulate and analyze the difference in gain of the single antena, 1x2, 1x4, 1x8 arrays that have been made. From the results obtained from Gain with single Gain 1.73 dB, Array 1x2 Gain 2.97dB, Array 1x4 Gain 5.5 dB, Array 1x8 Gain 7.46 dBA Single Microstrip antena has small dimensions that can work at high frequencies However, this single patch Microstrip Antena has a weakness in the amount of radiant power (Gain), and a large polarization angle, to reduce the weakness of this single patch Microstrip Antena.